On the hydrodynamic loading of marine cycloidal propeller during maneuvering. (May 2019) - Prabhu, J.J.; Dash, A.K.; Nagarajan, V.; Sha, O.P.
Abstract: In marine cycloidal propeller (MCP), the inflow velocity vector to the propeller blade continuously changes at different blade orbit angle. Earlier marine cycloidal propellers were installed on ships that mainly performed towing operations. Recently marine cycloidal propellers are being installed on large naval vessels, which spend lot of their operating hours in cruising. Therefore, the hydrodynamic loading on the blades both during cruising maneuvers need to be investigated. The flow characteristics around the propeller blade are computed numerically by panel method. Viscous effects on the flow are then estimated by boundary layer technique. The effect of rotating disc on viscous fluid is also investigated. The corrected flow characteristics are then used for estimating the hydrodynamic loading. The operating conditions that are critical for the loading of the blade and the support structure and some aspects of the maneuvering simulation at cruising speed are investigated.